Serial Clinical Scoring to Assess Transported Pediatric Patients. Issue 12 (5th December 2021) - Holt, Tanya; Parker, Kayla; Shaw, Adam; Hansen, Gregory
Abstract : Objectives: The objective of this study was to evaluate serial Transport Risk Assessment in Pediatrics (TRAP) scoring during pediatric critical care transport as a potential measure for specialized pediatric transport teams (PTTs). Methods: This was a retrospective study with a provincial PTT from a tertiary hospital pediatric intensive care unit. All acutely ill children who were transported by the PTT between 2018 and 2019 were included in the study. The TRAP scores were measured at time of transport team arrival (TRAP1), time at arrival to tertiary center (TRAP2), and 4 hours postarrival to tertiary center (TRAP3). Results: A total of 300 transports were included. Patients' mean age was 54 months, with lower respiratory tract infection (40.7%) as the most common diagnosis. There were significant differences between TRAP1-TRAP2 ( P < 0.01) and TRAP1-TRAP3 ( P < 0.01), but not between TRAP2-TRAP3 ( P = 0.67). The most significant improvements of ΔTRAP1-TRAP2 scores were seen in septic shock (mean, 2.0; SD, 1.7). Conclusions: The TRAP scores improved following the PTTs' arrival to acutely ill children, particularly with sepsis. Serial TRAP scoring may present a system for evaluation of team performance and/or characterize disease states that are positively impacted by PTTs. Future prospective evaluation is needed to validate TRAP for this purpose.